Bonding of immiscible Mg/steel by butt fusion welding. (December 2018) - Song, Gang; Li, Taotao; Chi, Jiayu; Liu, Liming
Abstract: An appropriate intermetallic compound interface layer that can achieve improved lattice matching for Mg and Fe immiscible welding system is difficult to select and prepare. Lattice matching strengthening by promoting the diffusion of alloy elements in the IMC could be employed when the IMC layer is obtained. Immiscible Mg and Fe were bonded by laser-gas tungsten arc welding with Ni interlayer. Nanoscale (Al, Mg) (Ni, Mn, Fe) intermetallic-based and α-(Fe, Ni) solid solutions were formed at the interface. The interplanar misfit for the (110)(Al, Mg) (Ni, Mn, Fe) ||(0002)Mg system was reduced by 42.2% with the diffusion of alloy elements in the Al-Ni interface layer. Graphical abstract: Unlabelled Image